YY1 Promotes Telomerase Activity and Laryngeal Squamous Cell Carcinoma Progression Through Impairment of GAS5-Mediated p53 Stability - Wei, Xudong; Liu, Fenglei; Jiang, Xuelian; Xu, Xiaoyan; Zhou, Tianhao; Kang, Chengfang (Frontiers in Oncology, 2021)
Yin Yang 1 (YY1) is a key transcription factor that exerts functional roles in the cell biological process of various cancers. The current study aimed to elucidate the role and mechanism of YY1 in laryngeal squamous cell carcinoma (LSCC). YY1 mRNA and protein expression in human LSCC cell lines was detected by RT-qPCR and Western blot analysis. An interaction of YY1, GAS5, and p53 protein stability was predicted and confirmed by bioinformatics, ChIP, Co-IP, RIP, and FISH assays. Following loss- and gain- function assays, LSCC cell proliferation, colony formation, cell cycle, telomere length and telomerase activity were evaluated by CCK-8 assay, colony formation assay, flow cytometry, and PCR-ELISA, respectively. Nude mice were xenografted with the tumor in vivo. LSCC cell lines presented with up-regulated expression of YY1, downregulated GAS5 expression, and decreased p53 stability. YY1 inhibited the expression of GAS5, which in turn recruited p300 and bound to p53, thus stabilizing it. Moreover, YY1 could directly interact with p300 and suppressp53 stability, leading to enhancement of cell proliferation, telomere length and telomerase activity in vitro along with tumor growth in vivo. Collectively, YY1 can stimulate proliferation and telomerase activity of LSCC cells through suppression of GAS5-dependent p53 stabilization or by decreasing p53 stability via a direct interaction with p300, suggesting that YY1 presents a therapeutic target as a potential oncogene in LSCC development and progression.